Do Financial Literacy and Technology Affect Intention to Invest in the Capital Market in the Early Pandemic Period? - Nabila Na'ma Aisa (Journal of Accounting and Investment, 2021)
Research aims: This paper discusses the effect of financial literacy and automatic investment technology on intention to invest in the capital market during the early pandemic.Design/Methodology/Approach: The research population was students studying economics and finance in institutions located in Yogyakarta Special Region Province. The sample of 384 respondents was obtained through questionnaires distributed online. To test the impact of financial literacy and automatic investment technology on intention to participate in the capital market, multiple linear regression was used.Research findings: The researchers found that financial literacy and automatic investment technology affected students’ intention to invest in the capital market. The number of students with a moderate level of financial literacy score dominated, followed by the students with low and high literacy scores. Besides, students’ background in economic and finance appeared inadequate to solely determine the financial literacy score.Theoretical contribution/Originality: This paper contributes to the investment area, especially related to the automatic investment technology “Robo advisor,” that is still rarely studied yet, which will be a significant issue in the future. It also provides empirical results, which explain the investment intention through financial literacy. Moreover, this study was conducted during the massive growth of investors in Indonesia during the pandemic.Practitioner/Policy implication: This study provides a useful reference to the financial sector, especially the capital market. Inclusive programs regarding financial literacy should be expanded for wider society to enhance their knowledge and dismiss lack of confidence in capital market participation. Private sectors providing automatic investment technology are suggested to continue developing a more convenient application to be accessible by a broader range of society.Research limitation/Implication: The research included only students as the sample; hence, further research may use a larger area of the sample with various backgrounds and ages. Other determinants, such as norms, environment, risk, and more advanced financial literacy measurement, can also be added to enrich future studies and literature.